Factores asociados al síndrome de burnout en profesionales de enfermería durante la pandemia por COVID-19 - Azcárate Silva, Felipe David (2022)
This study chooses to determine the association between personal and work factors, and Burnout syndrome in nursing professionals at the Chepén Support Hospital, within the framework of the COVID-19 pandemic in the different hospitalization services. It is descriptive, quantitative, non-experimental, correlational and cross-sectional, with a sample population of 45 nurses. Regarding the collection of information, a questionnaire on labor factors and the presence of Burnout syndrome was applied. The data obtained were analyzed with the SPSS V25 program. The CHI square (X2) statistical test was applied, with a 95% confidence interval at a significance level of 5%. Finally, we reach the conclusion that the nursing professionals evaluated have been affected to a greater extent at a moderate level and to a lesser extent at a mild level; Therefore, their performance at the work level will be affected.